Aristotle's Alternative to Enduring and Perduring: Lasting. Issue 2 (September 2022) - Pemberton, John M.
Abstract : Although Aristotle does not explicitly address persistence, his account of persisting may be derived from a careful consideration of his account of change. On my interpretation, he supposes that motions are mereological unities of their potential temporal parts – I dub such mereological unities 'lasting'. Aristotle's persisting things, too, are lasting, I argue. Lasting things are unlike enduring things in that they have temporal parts; and unlike perduring things in that their temporal parts are not actual, but rather are potential. Lasting, that is Aristotle's persisting, is thus a distinctive alternative to enduring and perduring. I assess this alternative showing it to be attractive.